Analisis Pengukuran Kinerja Perusahaan Dengan Konsep Balanced Scorecard - Fitrianingrum, Dina; Sulastiningsih, Sulastiningsih (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2016)
The objective of the research is to evaluate performance of Madubaru firm. This research use the methode of Balanced Scorecard which balancing measurement of non finance performance and finance performance. In the perspective learning and growth emphasize on the education and employees training, and also employees satisfaction. In the perspective of internal business process, it emphasize at the the level of success and organizational development. In perspective of customer emphasize at the customer satisfaction. In perspective of finance can see from finance ratio. The research have result learning and growth perspective with good performance, internal business process perspective with very good performance, customer perspective with enough performance, financial perspective estimation with good performance. At general we can assesd performanced of Madubaru firm is good and expected to be improved again. Keyword : Balanced Scorecard, Learning and Growth Perspective, Internal Business Process Perspective, Customer Perspective, Financial Perspective.